ANALISIS KUALITAS LAYANAN RAWAT JALAN DI PUSKESMAS X KOTA SEMARANG MENGGUNAKAN INTEGRASI SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS - Muhammad Iqbal; Rizqulloh, Lutfiyah; Pradana, Firmansyah Kholiq (LPPM Universitas Awal Bros, 2025)
The high level of service utilisation at the X Health Centre in Semarang City requires a comprehensive evaluation of service quality to ensure that it meets patient expectations and perceptions. This study aims to analyse the quality of outpatient services at the X Health Centre in Semarang City using an integrative approach that combines the SERVQUAL model and Importance-Performance Analysis (IPA). This study is a quantitative, observational, descriptive-analytical design. The study population comprised an average of 195 outpatient visits per month, and a sample of 66 respondents was selected using the Slovin formula. Data collection was conducted using the SERVQUAL questionnaire, which measures five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis involved calculating perception, expectation, and SERVQUAL gap values, and mapping IPA attributes. The results showed that the dimensions of tangibles, assurance, and some aspects of reliability and empathy were in the strong category, indicating that service performance had met or exceeded patient expectations. However, the responsiveness dimension showed the most significant negative gap, particularly in indicators of service waiting time, access to complaint submission, and the speed of information provision. These findings indicate the need to prioritise improvements in operational aspects and service flow management. The conclusion of this study confirms that the integration of SERVQUAL and IPA is effective in identifying the strengths and weaknesses of outpatient service quality at Puskesmas X. It is recommended that Puskesmas focus on improving the dimensions of responsiveness and reliability, as well as conducting periodic service quality evaluations to enhance patient satisfaction and trust continuously. Keywords : SERVQUAL, Importance Performance Analysis, Community Health Center, Patient Satisfaction